Hadith #3685 - Sahih al-Bukhari - Abu As-Safar (Sahih al-Bukhari)
I heard Ibn `Abbas saying, “O people! Listen to what I say to you, and let me hear whatever you say, and don’t go (without understanding), and start saying, ‘Ibn `Abbas said so-and-so, Ibn `Abbas said soand- so, Ibn `Abbas said so-and-so.’ He who wants to perform the Tawaf around the Ka`ba should go behind Al-Hijr (i.e. a portion of the Ka`ba left out unroofed) and do not call it Al-Hatim, for in the pre-Islamic period of ignorance if any man took an oath, he used to throw his whip, shoe
Grade: Sahih